2020
DOI: 10.2147/copd.s267289
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Impact of COPD on in-Hospital Outcomes in Patients with Takotsubo Cardiomyopathy</p>

Abstract: Chronic obstructive pulmonary disease (COPD) is a known comorbidity of takotsubo cardiomyopathy (TCM), and COPD exacerbation is a potential triggering factor of TCM. The association between COPD and in-hospital outcomes and complications among TCM patients is not well established. We sought to assess the effect of COPD on hospitalized patients with a primary diagnosis of TCM. Methods: We conducted a retrospective cohort study in patients with a primary diagnosis of TCM with or without COPD using the latest Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The result was generated after patients were propensity-matched in a 1:2 target ratio (678 patients in the COPD-TCM group and 1070 in the non-COPD-TCM group) to avoid bias. 112 Another study of 14 639 TCM patients found that COPD was associated with greater in-hospital mortality (OR 1.444, 95% CI 1.140-1.829). 30 In addition, a study by Kato et al found that compared with those without lung disease, TCM patients with acute pulmonary triggers had greater 5 year mortality (HR 2.12, 95% CI 1.33-3.38), whereas chronic lung disease had no effect on mortality.…”
Section: Factors Of Takotsubo Cardiomyopathymentioning
confidence: 98%
See 2 more Smart Citations
“…The result was generated after patients were propensity-matched in a 1:2 target ratio (678 patients in the COPD-TCM group and 1070 in the non-COPD-TCM group) to avoid bias. 112 Another study of 14 639 TCM patients found that COPD was associated with greater in-hospital mortality (OR 1.444, 95% CI 1.140-1.829). 30 In addition, a study by Kato et al found that compared with those without lung disease, TCM patients with acute pulmonary triggers had greater 5 year mortality (HR 2.12, 95% CI 1.33-3.38), whereas chronic lung disease had no effect on mortality.…”
Section: Factors Of Takotsubo Cardiomyopathymentioning
confidence: 98%
“…The result was generated after patients were propensity‐matched in a 1:2 target ratio (678 patients in the COPD‐TCM group and 1070 in the non‐COPD‐TCM group) to avoid bias. 112 Another study of 14 639 TCM patients found that COPD was associated with greater in‐hospital mortality (OR 1.444, 95% CI 1.140–1.829). 30 In addition, a study by Kato et al .…”
Section: Factors Affecting Prognosis Of Takotsubo Cardiomyopathymentioning
confidence: 99%
See 1 more Smart Citation
“…The variables in our study include patient demographics (age, sex, race, household income, primary payer for the hospitalization) and hospital demographics (hospital type, hospital size and region). To further reduce selection bias, we included common cardiovascular comorbidities, such as smoking, hypertension, obstructive sleep apnea (OSA), peripheral artery disease (PAD), and other reported risk factors for TCM including chronic obstructive pulmonary disease (COPD), 21,22 anxiety 23 and depressive disorders, 18 obesity, 24 diabetes mellitus (DM), 25 chronic kidney disease (CKD) 26 and sepsis. 27 In-Hospital Outcomes…”
Section: Variablesmentioning
confidence: 99%
“…9 In addition, previous studies revealed that many comorbidities could affect the outcomes of TCM, such as obesity, 10 hyperlipidemia, 11 diabetes mellitus (DM), 12 depressive disorders, 13,14 chronic kidney disease (CKD), 15 and chronic obstructive pulmonary disease (COPD). 14,16…”
Section: Introductionmentioning
confidence: 99%